VEGETATIF GROWTH OF DENDROBIUM ORCHID (Dendrobium sp.) ON ZEOLITE APPLICATION AS MEDIA PLANTING AND LIQUID FERTILIZER SUPPLEMENT - Azlina Heryati Bakrie (Jurnal Zeolit Indonesia, 2008)
To determine the growth seeds of Dendrobium plant with mixture application media of coconut coir, fern, zeolite, and liquid fertilizer supplement have been done by the research in greenhouse Agricultural Faculty, University of Lampung. The treatment was arranged in a 2x5 factorial. The treatment was arranged in Randomized Perfect Design Group, with three replications. The first factor is mixture of growth media: coconut coir and fern (m1); coconut coir, fers, and zeolite (m2). The second factor is the application of liquid fertilizer supplement Hortigro Green with 5 levels of concentration: 0.5 g l-1 (h1); 1 g l-1 (h2), 1.5 g l-1 (h3), 2 g l-1 (h4); and 2.5 g l-1 (h5). The results showed that the mixture media of coconut coir, fern, and zeolite is producing bulb Dendrobium higher of 1,15 cm (16,39%) than without giving zeolite. Application of Hortigro fertilizer until 2,5 g l-1 still increasing the bulb height, leaf number, and length of the top three leaves of Dendrobium linearly. Application of Hortigro fertilizer every 1 g l-1 on a mixture media of growth with zeolite increasing the length of the top three leaves of 0.49 cm while in mixture growing of media without zeolite was increasing the length top three leaves of 1.63 cm. Application of zeolite in a mixture growing media was producing root structure better than the application without zeolite (Fig. 4).